Hydrazide-hydrazones of 3-methoxybenzoic acid and 4-tert-butylbenzoic acid with promising antibacterial activity against Bacillus spp. (1st November 2016) - Popiołek, Łukasz; Biernasiuk, Anna
Abstract: A series of 28 hydrazide-hydrazones of 3-methoxybenzoic and 4- tert -butylbenzoic acid were synthesized and screened in vitro against the panel of reference strains of bacteria and fungi with the use of the broth microdilution method according to EUCAST and CLSI guidelines. Five of the synthesized compounds were found to exhibit high bacteriostatic or bactericidal activity against Gram-positive bacteria. The antimicrobial activity of compounds13, 14, and16 against Bacillus spp. was higher than that of commonly used antibiotics, like cefuroxime or ampicillin.